2015
DOI: 10.1155/2015/727401
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Predictors of Cardiovascular Mortality

Abstract: Cardiovascular diseases are the main causes of mortality. Sudden cardiac death may also appear in athletes, due to underlying congenital or inherited cardiac abnormalities. The electrocardiogram is used in clinical practice and clinical trials, as a valid, reliable, accessible, inexpensive method. The aim of the present paper was to review electrocardiographic (ECG) signs associated with cardiovascular mortality and the mechanisms underlying those associations, providing a brief description of the main studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 85 publications
1
33
0
6
Order By: Relevance
“…8,9 The study identified ECG and ECHO changes (Table 3) in considerable number of patients among whom left ventricular hypertrophy/dilatation followed by right sided heart dilatation which was clear manifestation of excess fluid overload and peripheral vascular resistance due to improper fluid excretion in CKD. In the ECG study by Mozos et al in 2015 and Shafi et al 10,11 recently in 2017, similar results were recorded as changes in CKD patients. These changes cannot be earmarked as specific for CKD but can be used as markers in predicting CVD severity or prognosis in CKD which is a scope for future research.…”
Section: Discussionsupporting
confidence: 52%
“…8,9 The study identified ECG and ECHO changes (Table 3) in considerable number of patients among whom left ventricular hypertrophy/dilatation followed by right sided heart dilatation which was clear manifestation of excess fluid overload and peripheral vascular resistance due to improper fluid excretion in CKD. In the ECG study by Mozos et al in 2015 and Shafi et al 10,11 recently in 2017, similar results were recorded as changes in CKD patients. These changes cannot be earmarked as specific for CKD but can be used as markers in predicting CVD severity or prognosis in CKD which is a scope for future research.…”
Section: Discussionsupporting
confidence: 52%
“…Полученные результаты близки к эпидемиологиче-ским данным, представленным бельгийскими автора-ми, которые показали, что частота выраженных изме-нений ST у мужчин и женщин составляет 1,6% и 2,7%, а аномальных зубцов Т -6,1% и 9,6%, соответствен-но [8]. Частота ишемических кодов в популяции Но-восибирска и Тюмени также была схожа с нашими дан-ными -6,8% и 5,1%, соответственно [4].…”
Section: The Prevalence Of Electrocardiographic Changes In Older Age unclassified
“…Значения распространенности НП, полученные нами на выборках ЭССЕ-РФ для старшего возрастного кон-тингента, оказываются выше, чем в других странах (0,8% у женщин и 1,8% у мужчин) [8,11] и чем у исследо-вателей SAHR (0,5% и 1,1%, соответственно) [6]. Воз-можно, это связано с более выраженным бременем ССЗ в регионах РФ и меньшей возможностью получения адекватной помощи.…”
Section: нарушение проводимости (нп)unclassified
“…Indeed, applying medical sensors has demonstrated a remarkable efficiency in treating multiple diseases such as retinal, gastric, and heart‐related diseases . Worth noting, in this respect, is that heart‐associated diseases turn out to stand as the major cause of death worldwide …”
Section: Introductionmentioning
confidence: 99%